Curriculum Relevance Of Arabic Language Education With Job Opportunities For Graduates In Indonesia/ ملاءمة مناهج تعليم اللغة العربية لفرص عمل الخريجين بإندونيسيا - Taufiq, Mirwan Akhmad; Hasanah, Durrotul; Yumanto, Muhammad Indra; Elbaghdadi, Zaki Abouelnasr (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The ever-growing dynamics of education require the proper strategic steps in dealing with changing user trends and graduate job vacancies. The Master's Program in Arabic Language Education seeks to take proactive measures regarding the relevance of curricula to the requirements of the world of work. This study aims to conduct a tracer study for graduates and users to reveal the suitability of the work field for graduates with the jobs targeted in the curriculum document, the waiting period for work, and the skills used in the field of Arabic teaching, and to reveal the suitability of the Arabic teaching curriculum in the master's degree to meet the challenges of the world. It is because of the user-oriented business that continues to grow. This research relied on the qualitative descriptive approach. Primary data was collected from 2018-2020 alums and users. Distributed questionnaires, interviews, and group discussions implemented data collection techniques. The data analysis technique reduces data, presents data, and draws conclusions. Some results of this study are that the graduates' work is 82% suitable with the curriculum documents; 63% of alums become Arabic language teachers in schools and colleges, 19% become government employees, and 18% work freelance out of education and Arabic fields. Then, the average waiting period to work is less than six months. The skill that has a significant impact on graduate employment is technology-based teaching skills. Arabic handwriting skills, especially Khat, and Islamic studies skills are considered to have a minor effect. This study recommends modifying this curriculum toward a technology-based Arabic teaching concept. The use of digital media in every single course must be the primary principle to avoid losing out to Arabic YouTubers. This curriculum should also strengthen research methodology and publish articles and books.